Four Gospels, one Jesus? a symbolic reading - Burridge, Richard A., 1955- (North Blackburn, VIC HarperCollins, 1994)
Includes bibliographical references and index.
Keywords: Jesus Christ -- biography -- history and criticism; Bible. N.T. Gospels -- criticism, interpretation, etc